Incorporation of antimicrobial peptides on functionalized cotton gauzes for medical applications. (20th August 2015) - Gomes, A.P.; Mano, J.F.; Queiroz, J.A.; Gouveia, I.C.
Highlights: Biofunctionalization of cotton gauzes with antimicrobial agents. AMPs incorporation on biofunctionalized cotton gauzes with chitosan and alginate. Chitosan/alginate multilayers on cotton samples were obtained by LbL technique. Abstract: A large group of low molecular weight natural compounds that exhibit antimicrobial activity has been isolated from animals and plants during the past two decades. Among them, peptides are the most widespread resulting in a new generation of antimicrobial agents with higher specific activity. In the present study we have developed a new strategy to obtain antimicrobial wound-dressings based on the incorporation of antimicrobial peptides into polyelectrolyte multilayer films built by the alternate deposition of polycation (chitosan) and polyanion (alginic acid sodium salt) over cotton gauzes. Energy dispersive X ray microanalysis technique was used to determine if antimicrobial peptides penetrated within the films. FTIR analysis was performed to assess the chemical linkages, and antimicrobial assays were performed with two strains: Staphylococcus aureus (Gram-positive bacterium) and Klebsiella pneumonia (Gram-negative bacterium). Results showed that all antimicrobial peptides used in this work have provided a higher antimicrobial effect (in the range of 4 log–6 log reduction) for both microorganisms, in comparison with the controls, and are non-cytotoxic to normal human dermal fibroblasts at the concentrations tested.